STUDI SIFAT MEKANIK KOMPOSIT PEG (POLYETHYLENE GLYCOL) - 4000 PENAMBAHAN 10 WT% SiO2 QUARTZ DARI PASIR ALAM DENGAN MENGGUNAKAN DYNAMIC MECHANICAL ANALYSIS (DMA) - Sefrilita Risqi Adikaning Rani (Universitas Islam Negeri Alauddin Makassar, 2021)
The mechanical properties of (Polyethylene glycol) PEG4000 +10 wt% SiO2 have been investigated using DMA (Dynamic Mechanical Analysis). SiO2 processed from natural sand was added as much as 10 wt % SiO2 as a filler to the composite and PEG-4000 as a matrix. The results show that the addition of SiO2 filler makes the mechanical properties of the PEG-4000 polymer as a matrix increase when influenced by temperature and frequency including shear modulus (G') and tensile modulus (E'). Composites (PEG4000 + 10wt% SiO2 quartz) are more resistant to tensile loads when viewed from their tensile modulus.